2.8k views
2 votes
Given the functions, f(x) = 4x3 - x2 + 1 and g(x) = x - 1, evaluate f(g(2)).

User Mesutozer
by
4.7k points

1 Answer

5 votes

Answer:

4

Explanation:

f(g(2)) means "put 2 into g(x) and then take that answer and put it into f(x)"

Given:


f(x)=4x^3-x^2+1

and


g(x)=x-1

Now, let's find g(2) first:

g(x) = x - 1

g(2) = 2 - 1

g(2) = 1

Now, lets put this into f(x). So we have:


f(x)=4x^3-x^2+1\\f(1) = 4(1)^2 - (1)^2 +1\\f(1) =4

That is f(g(2)) = 4

User Thomas L Holaday
by
5.5k points